2008
DOI: 10.1007/s00393-008-0318-1
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitative und ambulante physikalisch-medizinische Versorgung von Rheumakranken

Abstract: Rehabilitation and outpatient physiotherapy were investigated from the perspectives of patients suffering from rheumatoid arthritis (RA) or ankylosing spondylitis (AS) and of rheumatologists. In 2007, 204 outpatients with RA and 47 with AS at the Arthritis Center in Halle, Germany, and 117 rheumatologists from all over the country participated in two questionnaire surveys. Patients and rheumatologists gave predominantly positive judgements of physiotherapy, psychological interventions, and patient education pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“…Additionally, we then included 4 studies that were known to us [33], [34], [35], [36] but had not been identified through the MEDLINE search. A total of 8 studies were, therefore, included in the review [10], [25], [33], [34], [35], [36], [37], [38]. All studies were carried out exclusively in Germany, with the exception of one study that included a mixed population from the Netherlands and Germany [38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we then included 4 studies that were known to us [33], [34], [35], [36] but had not been identified through the MEDLINE search. A total of 8 studies were, therefore, included in the review [10], [25], [33], [34], [35], [36], [37], [38]. All studies were carried out exclusively in Germany, with the exception of one study that included a mixed population from the Netherlands and Germany [38].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used a longitudinal approach and two studies used a cross-sectional approach [35], [38]. Utilisation was assessed using questionnaire surveys [33], [37], [38], routine data [25], [35], [36] and health insurance records (10, 34). Further methodological issues are described in Table 1 (Tab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Einer Befragung von Rheumatologen und Patienten aus dem Jahre 2007 zufolge, erhielten in den letzten 12 Monaten vor der Befragung rund 11% der funktionell am meisten und 2-4% der weniger ausgeprägt beeinträchtigten Patienten mit RA Ergotherapie und/oder Funktionstraining/Rehabilitationssport [12]. Zink et al [18] erfassten im Rahmen der Kerndokumentation fast 9000 Patienten mit rheumatischen Erkrankungen.…”
Section: Situation Der Ergotherapeutischen Routineversorgung In Deutsunclassified
“…Nach welchen Faktoren werden derzeit die Patienten physiotherapeutisch versorgt, gibt es bestimmte Determinanten oder welche Faktoren sind f ü r die Verteilung der Leistungen verantwortlich? Mau und M ü ller [24] zeigen in ihrer Untersuchung, dass bei einem gro ß en Teil der Patienten trotz erheblicher Funktionseinschr ä nkung keine ambulanten physikalisch-medizinischen Interventionen verordnet werden. Als eine wichtige Ursache nennen die Autoren geringe Heilmittelrichtgr ö ß en.…”
unclassified